Descriptive Analysis of User-centered Usability Techniques to Health Technology Management - Brandão, M. R.; García, R. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2020)
The use of usability techniques to understand the user’s perception is essential in the evaluation and development of technological solutions in healthcare environments centered on the end user. In the incorporation of technologies in healthcare establishments, the management has become essential in terms of safety, reliability and efficiency for the patient. This article addresses the techniques of interviews, focus groups, surveys and the delphi method, bringing a general descriptive conceptual analysis of Human Factors Engineering techniques aiming to assist in the management of health technologies more efficiently and with quality for the patient. The techniques of data collection can be applied both in the pre commercialization stages of the technology, in the data collection of the user’s technological need and validation of prototypes of new solutions, and in the post-commercialization stages, analyzing the main usability problems, involving devices already commercially available. Each usability technique for data collection has its advantages and disadvantages, and it is necessary to analyze the objective of the research to determine the choice of the most appropriate method. This article addresses conceptually the possibilities of practices including all actors in the technological health process creates a collaborative, interdisciplinary and innovative ecosystem, with interaction of the technical area with the clinical, essential to develop better technological solutions in health, focusing on the end user’s needs. The application of these tools can assist the Clinical Engineering area in the discussion of strategies that may better use of technologies in patient care.